2015
DOI: 10.1186/s12905-015-0244-8
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health services for women with disability: a qualitative study with service providers in the Philippines

Abstract: BackgroundThe Philippines has ratified the United Nations Convention on the Rights of Persons with Disabilities and recently passed domestic legislation protecting the sexual and reproductive rights of people with disability. However women in the Philippines continue to report barriers to sexual and reproductive health services, and there is limited empirical evidence available to inform policy makers’ efforts to respond. This study aims to contribute to the available evidence by examining service providers’ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 18 publications
1
29
0
3
Order By: Relevance
“…Due to lack of interpreters, family members were the source of information and thus the women with disabilities remained on side track during assessment and management. 4 Participants of present study reported important role of family member as interpreter between the healthcare provider and the patient. It was noted that family members, especially husband and mother in law helped in postnatal care.…”
Section: Discussionmentioning
confidence: 82%
“…Due to lack of interpreters, family members were the source of information and thus the women with disabilities remained on side track during assessment and management. 4 Participants of present study reported important role of family member as interpreter between the healthcare provider and the patient. It was noted that family members, especially husband and mother in law helped in postnatal care.…”
Section: Discussionmentioning
confidence: 82%
“…limited access to health information, limited access to sex education programs, knowledge and education, cultural norms, religious beliefs, and familiarity [17][18][19][20][21]. In addition, sexual and reproductive health services toward individual with ID facing with the spectrum of discrimination and exclusion in low and middle-income countries besides their vulnerabilities [9,22].…”
Section: Discussionmentioning
confidence: 99%
“…The WHO Factsheet on Health and Disability 17 reports that the health needs of persons with disabilities are largely unmet and argues that more persons with disabilities look for health care than those without disabilities. A study in the Philippines 19 reported that girls and women with disabilities seeking SRH services face discrimination and negative attitudes at the hands of some health workers. An exposition on the SRH experiences of visually impaired women in Ghana 20 reveals how pregnant women and girls with disabilities were faulted and perceived as undeserving of motherhood, irrespective of whether they were married, or had experienced unwanted pregnancies.…”
Section: The Ghana Adolescent Reproductive Health Policy and Strategymentioning
confidence: 99%